Myasthenia and Antisynthetase Antibody Syndrome: A Case Report in Togo - GUINHOUYA Kokou Mensah; AGBA Lheleng; ANAYO Nyinevi Komla; BELO Mofou; BALOGOU Agnon Koffi (Journal of Neurological Research And Therapy, 2017)
Myasthenia is a rare neurological condition with risk of death in case of inappropriate management. The outcome of this pathology is very bad in developing countries with inadequate technical Platform. We underlined the main difficulties of diagnostic and the management of Myasthenie and antisynthetase antibody syndrome in a 44 years-old Togolese man.
Keywords: Mysthenia